MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA “CHEMONDRO”, MOTIVASI, DAN HASIL BELAJAR - Santi Santi; Leny Leny; Bambang Suharto (Vidya Karya, 2019)
Abstract. This study aims to determine whether there are significant differences in learning motivation and learning outcomes in students between the use of PjBL learning models assisted by Chemondro android-based chemistry learning media with expository learning models. In addition, it is aimed to determine students' responses to Chemondro media on colloidal material. Classes becaming the sample were class X-TKJ A and X-TKJ B at SMK Negeri 2 Banjarmasin. The method used is a quasi-experimental with descriptive and inferential analysis techniques. This research shows that there are significant differences in motivation and student learning outcomes in classes using the PjBL model compared to the expository model. The use of Chemondro media for colloidal material perceived positive responses from students. Keywords: Project Based Learning (PjBL), Chemondro, motivation to learn, learning outcomes, Colloid Abstrak. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan motivasi belajar dan hasil belajar yang signifikan pada peserta didik antara penggunaan model pembelajaraan PjBL berbantuan media pembelajaran kimia berbasis android Chemondro dengan model pembelajaran ekspositori. Selain itu, untuk mengetahui respon peserta didik terhadap media Chemondro pada materi koloid. Kelas yang menjadi sampel penelitian adalah kelas X-TKJ A dan X-TKJ B di SMK Negeri 2 Banjarmasin. Metode yang digunakan adalah quasi-experiment dengan teknik analisis deskriptif dan inferensial. Penelitiian ini menunujukkan adanya perbedaan motivasi dan hasil belajar peserta didik yang signifikan pada kelas yang menggunakan model PjBL dibandingkan dengan model ekspositori. Penggunaan media Chemondro materi koloid mendapat respon positif dari peserta didik. Kata kunci: Project Based Learning (PjBL), Chemondro, motivasi belajar, hasil belajar, Koloid